United Kingdom : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
This staff report on United Kingdom's (UK) 2013 Article IV Consultation highlights economic policies and development. The UK economy grew by about u percent in 2012. Net trade reduced growth by 0.6 percentage points of GDP, the biggest drag since 2005, and well above staff projections. Domestic fixed capital investment was essentially flat, leaving household spending the main source of private demand, but still substantially below long-run potential growth. In terms of production, construction has been particularly affected by the financial crisis, and the mining sector has been experiencing a secular decline, accelerated in part by temporary shutdowns in North Sea oil extraction.